Why people co-produce within activation services: the necessity of motivation and trust – an investigation of selection biases in a municipal activation programme in the Netherlands. (March 2016) - Fledderus, Joost; Honingh, Marlies
Activation services that aim at re-employment of jobseekers often suffer from 'creaming', i.e. selecting those who have the best qualifications to re-enter the labour market. New ways of delivery, such as co-production, are supposed to be less subject to selection mechanisms. To analyse whether co-produced activation programmes suffer from selection biases, participants in a local innovative activation programme ( n = 60) were compared to non-participants ( n = 18). Participants are more motivated in general and showed higher levels of generalized, municipal and interpersonal trust. Moreover, high general motivation relates to high levels of trust and perceived control. This indicates that there is indeed a selection bias within co-produced activation programmes. Therefore, it remains uncertain whether co-production is more successful in dealing with creaming than common types of service delivery. Points for practitioners: Public services, in the field of activation policies for instance, are increasingly delivered in a fashion that requires more responsibility and effort from users. This study shows that such demands elicit a selection of users. Professionals dealing with co-produced services should be aware that when they choose clients they are likely to leave out vulnerable individuals. In particular, when intrinsic motivation is an important selection criterion, those who have low levels of trust and perceived control will not be involved. Consequently, seemingly inclusive strategies could in fact lead to exclusion.